Pemanfaatan Aplikasi Google Maps sebagai Media Pembelajaran Geografi untuk Peserta Didik SMP dan SMA Sederajat - Sambonu, Ayundini Yuliantina; Sya, Ahman; Zid, Muhammad (STAI Auliaurrasyidin Tembilahan, 2023)
Limited geography learning media in schools sometimes makes students and teachers do field studies. But this will take quite a long time with high operational costs. This research aims to learn about using the Google Maps application as a learning medium in geography subjects for junior and senior high school students of the same level to understand better the characteristics and location of an area on the face of the earth. This research uses data collection methods related to the topic of discussion in this study, with articles, journals, and books and journals as the primary sources. The data is then reviewed, presented, and described to obtain appropriate and scientific conclusions. The results of the research show that geography learning media through Google Maps can clarify and broaden students' knowledge regarding conditions on the earth's surface so that, theoretically, it will be able to influence students so that their understanding of the material can be more in-depth and lasting.